Nurturing youth climate action: A blue carbon perspective - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2024)
It was announced at the COP27 Climate Conference in Sharm El-Sheikh (Egypt) in November 2022 that Amazon and Conservation International (with support from the Singapore Economic Development Board) will establish an International Blue Carbon Institute in Singapore. As Minister for Sustainability and the Environment, Grace Fu rightly pointed out during the launch in the Singapore Pavilion that “South-east Asia, with its vast stretches of mangroves and coastal ecosystems, has tremendous potential for blue carbon initiatives that will also support environmental protection, biodiversity conservation, and livelihoods and heritage of local communities” (The Straits Times, New blue carbon institute to be launched in Singapore, 15/11/2022). As educators involved in sustainability and smart city-related courses, we certainly welcome this new initiative. However, while the concept of blue carbon has gained recognition among scientists, policymakers, and environmentalists, it is not yet widely understood by the general public. In fact, from an educational standpoint, blue carbon is both an opportunity (e.g., in terms of mangrove regeneration) and a pedagogical challenge. Just like carbon trading or ESG reporting, ‘blue carbon,’ a term coined in 2009 to highlight the contribution of coastal vegetated ecosystems to climate change mitigation, is still a closed book for many youths. However, given the alarming new climate change projections, there should be a greater sense of urgency in raising awareness and building capacity so that our youths can appreciate their essential role in fighting climate change.